Metabolic engineering of parageobacillus thermoglucosidasius for sustainable production of fuels and chemicals - Madika, Abubakar (2023)
The continued reliance on fossil fuel reserves to meet global energy and chemical demands is unsustainable and faces challenges such as the limited supply of fossil fuels and environmental concerns due to the release of greenhouse gases (GHGs), the leading cause of climate change. Thus, alternative, more sustainable, environmentally friendly routes are needed to produce fuels and chemicals. One of the most promising and attractive options is the use of microbial fermentative processes to produce chemicals and fuels from renewable feedstocks, mainly lignocellulosic biomass. Presently, ethanol is the leading biofuel produced and used globally, primarily because it can be made by fermentation technology that has been available for a long time. However, there is a growing interest in developing processes for producing alternative, and superior biofuels to ethanol, such as isobutanol which has higher energy density, reduced vapour pressure and lower hygroscopicity. The thermophile P. thermoglucosidasius has a significant attraction as a chassis for producing fuels and chemicals from renewable lignocellulosic feedstock. Therefore, the work presented in this thesis focused on the metabolic engineering of Parageobacillus thermoglucosidasius NCIMB 11955 for the production of biofuels (ethanol and isobutanol) and the platform chemical 3-hydroxypropionate (3-HP). The lack of adequate and effective genetic tools has hindered the full exploitation of these bacteria and other thermophiles' potential. Hence, the first part of this study involved the characterisation of the pMTL60000 modular vector series. Followed by the successful implementation of a theophylline-responsive CRISPR/Cas9 genome editing tool for the metabolic engineering of P. thermoglucosidasius NCIMB 11955 to produce strains capable of producing ethanol efficiently as a primary fermentation product from barley straw hydrolysate. This study also achieved the engineering of P. thermoglucosidasius NCIMB 11955 to make the platform chemical 3-HP via the malonyl-CoA pathway using the native acetyl-CoA carboxylase (ACC) and heterologous expression of malonyl-CoA reductase (MCR) and malonate-semialdehyde reductase (MSR) from either Chloroflexus aurantiacus, Metallosphaera sedula, Sulfolobus tokodaii or Sulfolobus solfataricus. As part of this goal, the native catabolism of 3-HP in P. thermoglucosidasius NCIMB 11955 was investigated, and a strain incapable of 3-HP degradation was generated and represented an ideal chassis for future 3-HP production. Finally, the study also focused on isobutanol production via the consolidated bioprocessing (CBP) approach. While attempts and some progress were made to engineer P. thermoglucosidasius NCIMB 11955 to produce isobutanol from glucose, unfortunately, a significant titre of isobutanol was not achieved to pave the way for isobutanol production through CBP. Hence, further research efforts will be required to achieve this goal. The engineered strains of P. thermoglucosidasius NCIMB 11955 capable of either producing bioethanol, 3-HP or isobutanol could form the basis of a low-cost biomass processing and the production of biobased chemicals or fuels.